Tunable passively Q-switched thulium-doped fiber laser operating at 1.9 μm using arrayed waveguide grating (AWG) - Samion, M.Z.; Ismail, Mohammad Faizal; Muhamad, A.; Sharbirin, A.S.; Harun, Sulaiman Wadi; Ahmad, Harith (Elsevier, 2016)
Thulium-doped fiber lasers (TDFLs), operating in the 1.8–2.0 µm wavelength region, have been viewed as an important research topic, due to their potential in various fields of applications. However, the growing need to advance the development of applications in various fields for instance medicine and environment sensor, has led to a deeper and specific study of Q-switched TDFLs with wavelength tunability. In this paper, a stable, tunable Q-switched TDFL operating in a wavelength range near to 1.9 µm by exploiting the use of a multiwall carbon nanotube (MWCNT)-based thin film as a saturable absorber (SA), and the use of an arrayed waveguide grating (AWG) for wavelength tunability, is presented. The tuning range of the Q-switched pulses generated covered a wavelength range that spanned from 1871.6 nm to 1888.8 nm. The repetition rate of the generated Q-switched pulses covers a range of frequency starting from 41.19 kHz to 68.3 kHz with a change in pump power from 242.2 mW until 360.9 mW.